Interpreting Islamic Political Parties
XVIII, 302 p.
Keywords: Interpreting Islamic Political Parties offer a critical analysis and explanation of the evolution, institutionalization and current developments of Islamic political parties. The volume contains case studies of Islamic political parties in Algeria, Egypt, Indonesia, Kuwait, Lebanon, Malaysia, Maldives, Mauritius, Somalia, South Africa and Sudan.